Ultrasensitive RDX detection with commercial SERS substrates. (21st November 2013) - Almaviva, S.; Botti, S.; Cantarini, L.; Fantoni, R.; Lecci, S.; Palucci, A.; Puiu, A.; Rufoloni, A.
<x xml:space="preserve">Abstract</x> Surface‐enhanced Raman spectroscopy (SERS) measurements on 1, 3, 5‐trinitroperhydro‐1, 3, 5‐triazine were performed with a table‐top micro‐Raman system exciting the analyte with a diode laser emitting at 785 nm. The main Raman features of 1, 3, 5‐trinitroperhydro‐1, 3, 5‐triazine were clearly identified, and a careful optimization of acquisition parameters was performed in order to increase the overall sensitivity of the apparatus. The amount of the sampled substance was determined through the analysis of high‐resolution scanning electron microscope images of the substrate covered with the residual explosive and resulted to be of the order of few tens of picograms. This value demonstrates the applicability of commercial substrates to the ultrasensitive surface‐enhanced Raman spectroscopy detection of explosives, allowing for their identification in real time. Copyright © 2013 John Wiley & Sons, Ltd.